Case report: Treatment of intraductal papillary mucinous neoplasms located in middle-segment pancreas with end-to-end anastomosis reconstruction after laparoscopic central pancreatectomy surgery through a pigtail-tube-stent placement of the pancreatic duct - Liu, Guohua; Tan, Xiaoyu; Li, Jiaxing; Zhong, Guohui; Zhai, Jingwei; Li, Mingyi (Frontiers in Surgery, 2022)
Intraductal papillary mucinous neoplasm (IPMN) of the pancreas is one type of pancreatic cystic neoplasm. IPMNs can be classified into three types: main duct-IPMN (MD-IPMN), branch duct-IPMN (BD-IPMN), and mixed type-IPMN (MT-IPMN). It is universally accepted by most surgeons that patients who suffered from MD-IPMN with a high risk of malignant transformation should undergo surgical resection. However, a consensus on the best surgical strategy for MD-IPMN located in the pancreatic neck has still eluded the surgical community worldwide. Recently, one patient suffering from this condition in our Minimally Invasive Pancreas Center underwent a successful surgical procedure. In this case report, we performed a laparoscopic central pancreatectomy for this patient. During this surgical procedure, we used a method of end-to-end anastomosis reconstruction through a pigtail-tube-stent placement of the pancreatic duct. Before the construction of the remnant pancreas, the surgical margins of the frozen section should be negative. After surgery, the outcome of this case was satisfactory. No complications such as postoperative hemorrhage, abdominal infection, pancreatitis, delayed gastric emptying, and clinically relevant postoperative pancreatic fistula occurred, which demonstrated that this surgical strategy could achieve a good clinical therapeutic effect for the pancreatic neck MD-IPMN. The result of postoperative routine pathology confirmed the diagnosis of MD-IPMN. The pathological features also showed that there was a high degree of hyperplasia in the local epithelium, which indicated the necessity of surgical treatment.